Hubungan Kondisi Lingkungan Rumah dengan Kejadian Tuberkulosis (TB) Paru: Relationship with House Environmental Conditions Event of Tuberculosis (TB) Lungs - Yosua, Meko Indri; Ningsih, Fitriani; Ovany, Riska (Jurnal Surya Medika (JSM), 2022)
Pulmonary tuberculosis, or pulmonary TB, is an infectious disease caused by Mycobacterium tuberculosis (M. Tuberculosis). Pulmonary TB bacteria spread to other people through transmission or airflow (sputum of smear-positive pulmonary TB patients) when the patient coughs or sneezes. In addition, it impacts the individual and the sufferer's family, namely the psychological effect in the form of decreased support, anxiety, or low self-confidence. The World Health Organization (WHO), in its 2018 Annual report on global TB Control, stated that there were ten countries categorized as high-burden countries for pulmonary tuberculosis, namely Indonesia in third place with 842,000 TB cases. According to the WHO 2018, the incidence of tuberculosis in Indonesia in 2017 was 319 per 100,000 population, and the death rate for tuberculosis patients was 40 per 100,000 population. The condition of the home environment is very influential on the transmission of pulmonary TB disease. These include roofs, floors, walls, availability of windows, ventilation, lighting, and occupancy density. Objective: The purpose of this study was to determine the relationship between home environment conditions and the incidence of pulmonary TB. Using the literature review method. Search journals using an academic database, namely Google Scholar, published in 2018-2020 using Indonesian and English. The research analysis results showed that six research journals had a relationship with the relationship between home environmental conditions and the incidence of pulmonary tuberculosis. Based on the results of research using the literature review method, there is a relationship between home ecological conditions, including ventilation, occupancy density, and lighting, with the incidence of pulmonary tuberculosis (TB).